Globalization and Responsibility - Delic, Zlatan (IntechOpen, 2012)
The book "Globalization and Responsibility" consists of 8 chapters. The chapters in the book offer a decentered and dynamic terminology. They show that globalization consists of not only an objective process, but also of a lot of statements that define, describe and analyze the different experiences of the process. The chapters are written by authors and researchers from different academic disciplines, cultures and social contexts, therefore different experiences and scientific analyses on the consequences of globalization have been unified, starting from the multicultural and social epistemology to ethics of responsibility. Each chapter can be read separately, but in a complex, interconnected global universe of intertextuality of our world.